Attitudes and Practices on Covid-19 amongst Residents of Two States in Northern Peninsular Malaysia - Tan, Kim Tat; Kiew, Sin Yee; Bina Rai, Saraswathi (IIUM Medical Journal Malaysia, 2022)
INTRODUCTION: With the global evolution of Covid-19, and Malaysia’s efforts in containment, the onus of curtailing spread lies in the efforts of the residents to comply and adapt to the new social norms. Our aim was to study the attitudes and practices of the residents in two states in Northern Peninsula. MATERIALS AND METHODS: An analytical cross-sectional study conducted late October 2020. A pre-validated questionnaire via Google forms used. Sample size determined to be 385 for each state. Five-point Likert scale was used to cover 12 questions on attitude and 10 required practices. Data scored and converted into categorical data based on median value of good and bad attitude and practices respectively and analysed with SPSSv23. Statistically significant was p<0.05. With the scored data, Spearmans correlation was used to determine difference in attitude and practice and between the two states. RESULTS: Total of 834 respondents with 50.2% from Penang, mostly aged 20 to 30 years, green zone (40.9%), Chinese (52.6%), Malaysians (97.6%). Overall, 55.6% had good practice with 50.6% good attitude against Covid-19 prevention. Females, those aged 20 to 30 years, married and full-time workers, scored better in preventive actions. Attitude was not associated with any of the factors. Overall, 94.8% agreed to strict enforcement of social distancing and masking. A weak but positive, significant correlation between attitude and practice. CONCLUSION: Level of compliance to new norms is good with no difference between the two states. We need to ensure the social norms are sustained by the community.